Improved power maxima point of photovoltaic system using umbrella optimizing technique under PSCs: An experimental study. Issue 10 (3rd May 2022) - Sharma, Amit Kumar; Pachauri, Rupendra Kumar; Choudhury, Sushabhan; Mahela, Om Prakash; Khan, Baseem; Gupta, Ankur Kumar
Abstract: This paper discusses the umbrella optimizing technique (UOT), a novel approach to track maximum power point (MPP) of a solar photovoltaic (PV) system under partial shading conditions (PSCs).Since PSCs have a direct impact on the power generated by PV modules, many researchers have developed a variety of maximum power point tracking (MPPT) approaches to address this issue. Perturb and Observe (P&O) is a traditional method for tracking the maximum power of a PV module under PSCs. The fundamental issue with this traditional technique is that the algorithm misleads the step size and chases the wrong direction under PSCs to track MPP. The proposed algorithm finds the maximum power peak among several observed peaks caused by partial shading of a PV module. At each instance, the proposed algorithm checks for local or global peaks and adjusts the duty cycle of the inverse SEPIC DC–DC converter accordingly.In experimental study, UOT shows better performance in terms of tracking efficiency, tracking time, output power and output current.It exhibits a power boost of 3.39–4.14% with 9.09–16.66% faster tracking in different PSCs. A comparison of different optimization techniques illustrates that the UOT has higher tracking performance.